Havarie by Philip Scheffner: an Experiment in Erratic Empathy (Itinera, 2018)
In recent decades, many studies have been published on the topic of empathy across a range of disciplines. Being empathic is today almost a social duty, amplified by the possibilities enabled by new media in terms of getting directly in contact with stories and experiences of distant people simultaneously. The general trend is arguably that of focusing on the fusional relation between subject and object, without taking into account the distance and conflict implicit in sensing the other. The latest film of the Berliner visual artist Philip Scheffner, Havarie (2016), offers some compelling and fresh cinematic devices to challenge other kinds of empathic relation with the spectator, focusing on an erratic temporality that avoids striking actions and takes position against the idea of one, unique, right image to represent reality.